Vers une conception centrée sur l’utilité - Emilie Loup-Escande (Activités)
The main objective of this thesis is to support and to improve, with utility in consideration, the design process of artifacts in the context of emerging technologies. It was realized in the context of a Research-Action conducted as part of a real design project called 3DChild, which resulted in a virtual reality based software named “Appli-Viz’3D”.To meet our objective, we have chosen to focus on how utility is effectively dealt today in design community. Two main concerns guided our work. The first one was to analyze how utility and requirements are taken into account in design. From this point of view, we were interested in models, methods and tools used or advocated in marketing, industrial engineering, requirement engineering, software engineering, industrial design and ergonomics of design activities. We also explored representations of different profiles of designers on the utility and key elements in the process of construction of requirements. The second main interest was to study the effective contribution of stakeholders – designers and users – to the design of innovative artifacts through empirical studies. For this second line of research, we first aimed to analyze the global dynamics of the process of participative and continuous co-construction of requirements. We then focused on more specific issues of this process. We were particularly interested in the identification of requirements and in the proposal of specifications by different designers’ profiles. We finally studied the prioritization of requirements by different users’ profiles and the development of requirements, during the sessions of evaluation of the software Appli-Viz’3D in a participative context.At the end of this work, we propose two methodological contributions : a model of utility-centered design and an extension of a design method that is the I²I method. The model of utility-centered design is original because it is a framework to analyze, help or guide the inclusion of the utility in the design process. It theorizes the existence of two universes of utility : the prospective and retrospective universes. It formalizes the idea that the design involves a continuous dialectic between these two universes from the “analysis” phase where utility, form and detail of the software remain vague and speculative, to the “evaluation and test” phase where the final form is proven and continues to evolve in use. We propose also an extension of the I²I method in order to facilitate the integration of the user in the design process. In this sense, it is a methodological tool which aims to guide VR engineers to design products focused not only on the features, but also on the needs and expectations of end users. Our recommendations involve the integration of human specialists to achieve these steps.These methodological frameworks may provide tools for the Living Labs belonging to the European Network of Living Labs (EnoLL) supported by the European Commission. The objective of the Living Lab is to engage communities of users as soon as possible in the design process to co-create, explore, experiment and evaluate services, products or new uses before the implementation of an artifact. Their particularity is to establish a strong participatory dimension, because the end users, for whom the new product (or service) is built, is involved in the early stages of the design process, and their needs are taken into account throughout the project.